2017
DOI: 10.4236/jss.2017.510017
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Quality of Life in Elderly Population

Abstract: The elderly represent a population group that requires a specific and integral approach that promotes its wellbeing and health. There are contextual factors experience during this life stage, such as the generation of diseases, which can influence negatively central aspects of life. One of the constructs that could be affected by these factors is the Quality of Life (QOL). The interaction between the contextual variables and QOL is mediated by the Coping Strategies (CS) that the individual applies to cope with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The results of the multiple linear regression test in this study found that coping strategies that focus on emotions positively affect the quality of life of the elderly. This is in line with the results of research conducted by León-Navarrete et al (2017) found that the elderly who tend to use emotion-focused coping strategies will have a better quality of life score than the elderly who use problem-focused coping strategies. Based on the results of research conducted by Rohmah, Purwaningsih, and Bariyah (2012) found the results that the factors that affect the quality of life of the elderly include physical factors, psychological factors, social factors, and environmental factors and the most influencing factors are psychological factors.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the multiple linear regression test in this study found that coping strategies that focus on emotions positively affect the quality of life of the elderly. This is in line with the results of research conducted by León-Navarrete et al (2017) found that the elderly who tend to use emotion-focused coping strategies will have a better quality of life score than the elderly who use problem-focused coping strategies. Based on the results of research conducted by Rohmah, Purwaningsih, and Bariyah (2012) found the results that the factors that affect the quality of life of the elderly include physical factors, psychological factors, social factors, and environmental factors and the most influencing factors are psychological factors.…”
Section: Discussionsupporting
confidence: 90%
“…Coping generally refers to the cognitive and behavioral efforts (e.g., emotion regulation and problem solving) implemented to modulate internal or external demands that are appraised as taxing or exceeding personal resources ( Lazarus and Folkman, 1984 ; Endler and Parker, 1990 ; Garnefski et al, 2001 ). Adaptive coping skills are thought to be critical for adaptation at old age ( Gamrowska and Steuden, 2014 ; MacLeod et al, 2016 ) and have been associated with higher QoL ( Hildon et al, 2010 ; Rey and Extremera, 2016 ; León-Navarrete et al, 2017 ). Two recently developed instruments that capture various cognitive (emotion regulation) and behavioral coping strategies are the Positive Appraisal Style Scale (PASS) and the Behavioral Coping Scale (BCS).…”
Section: Introductionmentioning
confidence: 99%
“…It is a dynamic distinctive characteristic that may change according to the contextual situation. Consequently, coping strategies, resilience, and social participation can be considered cognitive and behavioral tools that can help older adults cope with life changes resulting from aging [ 73 ]. Furthermore, according to the theory of activity for successful aging, to preserve old roles, one must have new roles to be discovered or new things must be innovated [ 74 ].…”
Section: Discussionmentioning
confidence: 99%